ESG and Financial Scandals: The Role of Investor Attention in Curbing Misconduct in Indonesia’s Banking Industry - Indah Sri Lestari; Wulan Budi Astuti; Ratiningsih Ratiningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) performance on financial misreporting, with investor attention as a moderating variable in banking companies listed on the Indonesia Stock Exchange during the 2019–2022 period. The theoretical framework is grounded in Agency Theory and Legitimacy Theory to explain the role of ESG as an internal control mechanism and a means of gaining external legitimacy. The research employs a quantitative approach using secondary data from annual reports and sustainability reports. Financial misreporting is proxied by earnings management measured through discretionary accruals, while ESG performance is assessed using the GRI Standards index, and investor attention is proxied by institutional ownership. Data analysis was conducted using multiple regression and Moderated Regression Analysis (MRA). The findings reveal that all three ESG dimensions (environmental, social, and governance) have a significant negative effect on earnings management. Institutional investor attention is found to strengthen the negative relationship between environmental and social aspects with earnings management, but weaken the influence of governance. These results indicate that institutional investors tend to be more responsive to environmental and social issues compared to governance aspects. Practically, this study provides empirical evidence that ESG implementation can serve as a control instrument against financial misreporting in the banking sector, while theoretically enriching the literature on investor moderation in the relationship between ESG and earnings management practices.